Social robotics in music education: A systematic review - Martinez-Roig, Rosabel; Cazorla, Miguel; Esteve Faubel, José María (Frontiers in Education, 2023)
Introduction Social robotics applied to the educational context deals with proposals that start from the present to shape the future of what training in a specific subject can be. On this occasion, the aim is to investigate the connection between the utilization of social robots and the teaching–learning processes that take place within a formal music education environment at any stage of education. Methods To carry out this research, the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) model served as a reference to perform a systematic review of articles published in two of the most important scientific databases, Web of Science (WoS) and Scopus, since 2015. Results A total of four articles fulfilled the inclusion criteria. Discussion Our findings attest that social robotics still remains a practically unknown topic. Hardly any experiences have been developed in classrooms. In general, it is considered necessary for education, and more specifically for music, not to be left out of the developments in social robotics. This technology, which is increasingly present in various areas of our society, responds to the objective of defining the 21st century, and musical education is part of it.